2010
DOI: 10.1111/j.1464-410x.2010.09514.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the treatment of localized prostate cancer using supplemented cancer registry data

Abstract: Study Type – Therapy (cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? Variation in treatment of localized prostate cancer has been shown to exist according to demographic and clinical factors, patient and provider preference, and region of residence since there is no consensus concerning appropriate treatment. Between 1998 and 2002 the proportion of men choosing watchful waiting declined from 12.6% to 9.0% while those receiving brachytherapy (with or without external be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 33 publications
6
58
0
Order By: Relevance
“…This is similar to the trends reported by NCI SEER outcomes (45% radical prostatectomy, 24% total radiation, 8% hormonal, and 9% watchful waiting) 31 and within the regional trends reported by the Centers for Disease Control and Prevention (CDC) National Program of Cancer Registries (NPCR) Patterns of Care (PoC1) study. 32 Once prostate cancer was detected, we also observed a decrease in the age of surgery with successive decades, with the average age of surgical intervention as early as 63 years for the current decade and more conservative treatment likely for older age at cancer diagnosis.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to the trends reported by NCI SEER outcomes (45% radical prostatectomy, 24% total radiation, 8% hormonal, and 9% watchful waiting) 31 and within the regional trends reported by the Centers for Disease Control and Prevention (CDC) National Program of Cancer Registries (NPCR) Patterns of Care (PoC1) study. 32 Once prostate cancer was detected, we also observed a decrease in the age of surgery with successive decades, with the average age of surgical intervention as early as 63 years for the current decade and more conservative treatment likely for older age at cancer diagnosis.…”
Section: Discussionsupporting
confidence: 86%
“…In the results we present, we assume patients detected with non-metastatic prostate cancer are treated by radical prostatectomy. Radical prostatectomy is historically the most common treatment (Burkhardt et al 2002, Kawachi et al 2010, Hamilton et al 2011) and reported to be the best treatment in terms of expected QALYs for all the ages (Sommers et al 2007). It is also the only form of treatment for which the patients' cancer stages can be understood by pathological examination of the removed organ.…”
Section: Estimating Parametersmentioning
confidence: 99%
“…Prostate cancer is generally a disease of the elderly (70 years) and few men are diagnosed before the age of 50 years, the median age at being 68 years [3,4]. However, despite high incidence and mortality rates in the elderly, more studies suggest that the elderly are undertreated [5][6][7][8]. Recent guidelines state that age alone should not prelude patients from efficient treatment [9].…”
mentioning
confidence: 99%